Pharmacist-led education-based antimicrobial stewardship interventions and their effect on antimicrobial use in hospital inpatients: a systematic review and narrative synthesis. (September 2021) - Monmaturapoj, T.; Scott, J.; Smith, P.; Abutheraa, N.; Watson, M.C.
Summary: Background: Antimicrobial stewardship (AMS) programmes optimize antimicrobial use and address antimicrobial resistance. Pharmacists are often key agents of these programmes. The effectiveness of hospital-based AMS interventions when they are led by pharmacists, however, has not previously been reported. Aim: To evaluate the effectiveness of pharmacist-led AMS interventions in improving antimicrobial use for hospital inpatients. Methods: Standard systematic review methods were used. The search strategies and databases used in a previous Cochrane review were applied. Studies that reported pharmacist-led AMS interventions were included. Narrative synthesis was used to report the findings. PRISMA guidelines were followed. Findings: From 6971 records retrieved and screened, 52 full-text articles were included. Most studies were undertaken in teaching hospitals ( N  = 45) and many were conducted in North America ( N  = 27). Most interventions targeted junior or ward physicians and lasted between one and six months. All studies evaluated educational interventions often in combination with other interventions and reported improvements 'in compliance with target AMS practice'. Greater compliance was achieved with multiple interventions. Pharmacist-led interventions reduced the duration of antimicrobial therapy without increasing mortality. No consistency of evidence was achieved in relation to interventions and reduced duration of hospital stay, nor infections due to antimicrobial resistance or occurrence of Clostridium difficile . Conclusion: This is the first systematic review to evaluate the effectiveness of pharmacist-led AMS interventions in hospital inpatients. Education-based interventions were effective in increasing guideline compliance and reducing duration of antimicrobial therapy. Future hospital-based AMS programmes should consider the involvement of pharmacists to deliver and promote AMS interventions and programmes.